2019
DOI: 10.1007/s11524-019-00361-5
|View full text |Cite
|
Sign up to set email alerts
|

Urban Commuter Campus Students’ Perspectives on Sexual Violence: Implications for Response and Prevention

Abstract: Sexual violence victimization is unacceptably common in the US, with nearly half of women and one in five men reporting lifetime sexual coercion and/or unwanted sexual contact; much violence occurs in campus settings. The majority of sexual violence prevention programs designed to date were not developed around the needs of urban commuter campus students. The present study explored qualitatively how these students conceptualize sexual violence and prevention. Face-to-face in-depth interviews were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…As commuter students have lower Sense of Community, Awareness of Resources, and RTH, they may need additional or specialized training to increase their engagement on campus and with sexual violence prevention. Studies have suggested that prevention efforts should be tailored to meet unique commuter students' needs (Casey et al, 2019;Donne et al, 2019;Tsui & Santamaria, 2015). Furthermore, Donne and coauthors (2019) suggest that prevention efforts must address the intersecting identities that commuter students inhabit.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As commuter students have lower Sense of Community, Awareness of Resources, and RTH, they may need additional or specialized training to increase their engagement on campus and with sexual violence prevention. Studies have suggested that prevention efforts should be tailored to meet unique commuter students' needs (Casey et al, 2019;Donne et al, 2019;Tsui & Santamaria, 2015). Furthermore, Donne and coauthors (2019) suggest that prevention efforts must address the intersecting identities that commuter students inhabit.…”
Section: Discussionmentioning
confidence: 99%
“…When specifically asked about campus resources, respondents suggested the counseling center; other campus resources were not widely known. Although the research is lacking and mainly exploratory, the two qualitative studies cited here (Donne et al, 2019;Tsui & Santamaria, 2015) indicate that commuter students may be less aware of sexual violence resources when compared with students who live on campus-perhaps because they spend less time in the environment where these resources exist and have fewer opportunities to learn about them.…”
Section: Awareness Of Resourcesmentioning
confidence: 93%
See 3 more Smart Citations